The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/celc.201600906
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Annihilation Electrochemiluminescence of Cationic Helicene Luminophores

Abstract: The electrochemistry and annihilation electrochemiluminescence (ECL) of a series of chiral cationic helicene luminophores containing various substituents were investigated in acetonitrile solvent. The electrochemical characterization evidenced a systematic reversible reduction of cationic derivatives, whereas the oxidation could be reversible or not, depending on the nature of the core heteroatoms within the structure as well as the functional-group appendages. One of the key parameters governing the ECL inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
(18 reference statements)
1
16
0
Order By: Relevance
“…The procedures for the preparation of dioxa + [6]helicene, dipropyl and dioctyl diaza + [6]helicenes (diaza + (C 3 ) 2 and diaza + (C 8 ) 2 , respectively) have been previously reported . These derivatives were synthesized in one step from a single common advanced synthetic intermediate (See Figure S1 for structural and synthetic information) . Regioselective bromination and nitration of the dioctyl derivative afforded the diaza + (C 8 ) 2 Br 2 and diaza + (C 8 ) 2 (NO 2 ) 2 moieties, respectively .…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…The procedures for the preparation of dioxa + [6]helicene, dipropyl and dioctyl diaza + [6]helicenes (diaza + (C 3 ) 2 and diaza + (C 8 ) 2 , respectively) have been previously reported . These derivatives were synthesized in one step from a single common advanced synthetic intermediate (See Figure S1 for structural and synthetic information) . Regioselective bromination and nitration of the dioctyl derivative afforded the diaza + (C 8 ) 2 Br 2 and diaza + (C 8 ) 2 (NO 2 ) 2 moieties, respectively .…”
Section: Methodsmentioning
confidence: 59%
“…The electrochemical properties of cationic [6]helicenes can be modulated by the nature of the heteroatoms (O, N) contained within the helical core or via the addition of peripheral substituents . The study on cationic [6]helicenes as a molecular redox probes for thin voltammetric films described earlier for the detection of cations is extended here to anions.…”
Section: Resultsmentioning
confidence: 99%
“…Other applications in electrochemiluminescence or ion transfer voltammetry were also reported for some [4]-and [6]helicene cationic dyes but focused only on racemic compounds. 282,283,284 In collaboration with Prof. Naaman, Lacour investigated aza [4]helicenium derivative [260][BF 4 ] as potential organic spin filter owing to the Chirality Induced Spin Selectivity (CISS) effect. 285,286 Using magnetic conductive probe atomic force microscopy (mCP-AFM) and magnetoresistance measurements set-ups, the authors showed that spin specific electron conduction is measured on chiral helicenium films with an opposite preferred spin for (P) and (M) enantiomers (Figure 38).…”
Section: Applications Of Carbocationic Azahelicenesmentioning
confidence: 99%
“…However, the scarcity and high cost of the so‐called platinum groups metals requires searching for alternatives. In this context, polycyclic aromatic hydrocarbons are promising options despite their lower intrinsic solubility in water …”
Section: Introductionmentioning
confidence: 99%